2014
DOI: 10.12659/msmbr.890644
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathway by which the environmental toxin 4-Nonylphenol may promote an inflammatory response in inflammatory bowel disease

Abstract: Background4-Nonylphenol is a ubiquitous environmental toxin that is formed as a byproduct in the manufacturing and/or sewage treatment of regular household items. Previous work in our lab has implicated 4-NP in the progression of autoimmune diseases such as inflammatory bowel disease in which macrophages mistakenly attack the intestinal linings, causing chronic inflammation. Several key pro-and anti-inflammatory molecules have been shown to be involved in the manifestation of this disease, including IL-23A, CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The specific mechanisms leading to the inflammatory response of gouty arthritis are not fully understood. A study [ 10 ] found that the environmental toxin 4-Nonylphenol may promote an inflammatory response in inflammatory bowel disease, but whether it plays a role in the inflammatory response of the gout arthritis is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The specific mechanisms leading to the inflammatory response of gouty arthritis are not fully understood. A study [ 10 ] found that the environmental toxin 4-Nonylphenol may promote an inflammatory response in inflammatory bowel disease, but whether it plays a role in the inflammatory response of the gout arthritis is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been described as another plausible pathogenic factor in IBD. A recent experimental study revealed another potential pathogenetic factor of IBD; Kim et al found that in vitro, the administration of 4-nonylphenol up-regulates proinflammatory genes and decreases the expression of the anti-inflammatory genes in human cells lines, promoting gastrointestinal tract inflammation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be reasonably predicted that these genetic factors modify the intestinal epithelial cell barrier and have major effects on the function of innate and adaptive immune systems [ 18 ]. A wide variety of animal studies of mucosal inflammation that mimic IBD, as well as human IBD itself, strongly indicate the importance of Th1, Th2, and Th17 cells and their respective cytokines, as well as environmental toxins, in the development of this disease [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%